Optimum Compression to Ventilation Ratios in Cardiopulmonary Resuscitation: A Simulation Study (Journal of Fiber Bioengineering and Informatics, 2015)
Goal: The purpose of this paper is to investigate optimum compression to ventilation ratios in\rCardiopulmonary Resuscitation (CPR). Methods: Mathematical modeling approach is used. Equations\rdescribing oxygen, carbon dioxide exchange and blood flow as functions of the compression to ventilation\rratio during CPR are developed. The model is validated against normal physiology and animal studies of\rCPR. Then the model equations are solved to find the optimum compression to ventilation ratios for both\rprofessional and lay rescuers. As rescuer performance might vary greatly, Monte Carlo simulations with\rparameters of rescuer performance randomly chosen are performed to examine whether the optimum\rcompression to ventilation ratios achieved above fit most cases. Results: Results show that the optimum\rcompression to ventilation ratio is around 50:2 for professional rescuers, and is round 70:2 for lay rescuers.\rConclusion: The 30:2 compression to ventilation ratio, which is specified in International Guideline,\rmight not be optimum for professional rescuers, might be even worse for lay rescuers. It suggests the\r50:2 and 70:2 compression to ventilation ratios might be optimum for professional and lay rescuers\rrespectively. Significance: The 50:2 and 70:2 compression to ventilation ratios might maximize optimum\roxygen delivery to body tissue during CPR, and thus lead to better survival rates.
Keywords: Optimum Compression to Ventilation Ratios; Cardiopulmonary Resuscitation; Monte Carlo Simulations; Mathematical Modeling